Explicitation, Unique Items and the Translation of English Passives in Thai Legal Texts - Kenny, Dorothy; Satthachai, Mali (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2018)
Despite growing interest in the study of translation in Thailand, relatively little has been published on contemporary Thai translation practices. This study presents a first attempt to explore legal translation into Thai, using both a purpose-built parallel corpus of international treaties translated from English into Thai, and a monolingual corpus of non-translated Thai legislation. Drawing on previous corpus-based studies concerned with general features of translation, we ask whether there is evidence of explicitation (Becher 2010a) in our translated data and whether “unique items” (Tirkkonen-Condit 2002) are underrepresented. We pursue these questions through a study of the translation of the passive voice into Thai, and focus in particular on the Thai passive markers ถูก /thùuk/, โดน /doon/, and ได้รับ /dai-rup/, which we consider unique items in Thai. The study finds that, despite some writers’ antipathy to the passive voice in Thai, most English passives are translated into Thai using the passive voice, and that in those instances where the active voice is used in the translation, there is rarely any explicitation involved, as explicit agents are rarely added in Thai. We do not find any evidence to support the hypothesis that unique items are underrepresented in translation. On the contrary, the unique items studied appear to be overrepresented in translation into Thai.